Analysis of the impact of the introduction of market makers to the Japan securities dealers association quotations (JASDAQ) market. - Chin, Marcus Sin Wei. (2008)
The paper examines the impact of the introduction of market makers onto the Japan Securities Dealers Association Quotations (JASDAQ) market, occurred from December 1998 for the trading of selected stocks. Prior to this, all trading was carried out via an order-driven system. We investigate the impact of this change on relative bid-ask spreads, turnovers and any detectable liquidity premium.